TANGGUNG JAWAB PERUSAHAAN ATAS KECELAKAAN TONGKANG DALAM PERSPEKTIF DOKTRIN VICARIOUS LIABILITY DI SEMPADAN SUNGAI MAHAKAM - Sahim, Muhammad Sahril; Kurnia, Mahendra Putra; Wardana, Khristyawan Wisnu (Universitas Labuhanbatu, 2025)
The presence of buildings in the riverbank area of the Mahakam River that violate spatial planning regulations creates a legal dilemma when criminal acts of destruction are committed against such structures. This study aims to analyze the criminal liability for the destruction of illegal objects and to assess the potential application of restorative justice in resolving such cases. The research employs a doctrinal legal method using statutory and conceptual approaches, based on the provisions of the Indonesian Penal Code (KUHP) and regulations concerning riverbank spatial planning. The findings indicate that although the damaged object is located in an illegal area, the owner may still be regarded as a victim if the element of malicious intent by the perpetrator is fulfilled. Therefore, restorative justice emerges as a relevant alternative to achieve balanced justice between victim and offender.Keywords: Destruction, Restorative Justice, Criminal Law, Riverbank Zone